Determining “Professionalism of Dental Students at Various Academic Levels by PSCOM Scale” - Khizer Mehmood, Muhammad Imtiaz, Hina Ali, Salima Naveed Manji, Ayesha Ashraf (Pakistan Journal of Medical & Health Sciences, 2023)
Background/Introduction: Professionalism is one critical cornerstone of a successful academic program and considered to be the mainstay of health care provision. It is of great importance in the life of dentists because it plays a significant factor of interpretation and prediction of human behavior in various contexts of social and clinical practice. The purpose of this study was to determine professionalism of dental students at various academic levels by PSCOM scale. Methods: This is a descriptive cross-sectional study, the participants consisted of undergraduate dental students at various academic levels. The study was conducted between 29th of December 2021 to 10th of June 2022 at various dental colleges of Pakistan. A survey questionnaire was submitted to all participants to collect data to assess their professionalism through a validated PSCOM Scale. Results: The total number of participants were 403 containing 129 (32%) of men and 236 (58.6%) of women. The minimum age of the respondents in the research sample was 18 and the maximum age was 28 years. The average value of professionalism is 2.934 for BDS1, 3.045 for BDS2, 2.959 for BDS3 and 3.013 for BDS4 respectively. The average value of sub components of professionalism is 3.044 for accountability, 2.945 for altruism, 3.038 for duty, 3.038 for excellence, 2.964 for honesty and integrity and 2.976 for respect. Keywords: Professionalism; academic levels; PSCOM scale; dental students; competency; dental care; curriculum